Evaluate: ∫ 0 1 ln ( x ) ln ( 1 − x ) d x
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
@Joseph Newton AMAZING!!!! I solved it by differentiating the Beta Function........ similar to Sir Mark's solution....!!
Did the exact same
I = ∫ 0 1 ln x ln ( 1 − x ) d x = ( x ln x − x ) ln ( 1 − x ) ∣ ∣ ∣ ∣ 0 1 + ∫ 0 1 1 − x x ln x − x d x = x → 0 lim ( − ln x ) + ∫ 0 1 1 − x x ln x d x − ∫ 0 1 1 − x x d x = − x → 0 lim ln x − ∫ 0 1 ( ln x − 1 − x ln x ) d x − ∫ 0 1 x 1 − x d x = − x → 0 lim ln x − ( x ln x − x ) ∣ ∣ ∣ ∣ 0 1 + ∫ 0 1 1 − x ln x d x − ∫ 0 1 ( x 1 − 1 ) d x = − x → 0 lim ln x + 1 + ∫ 0 1 x ln ( 1 − x ) d x − ( ln x − x ) ∣ ∣ ∣ ∣ 0 1 = − x → 0 lim ln x + 1 − Li 2 ( 1 ) + 1 + x → 0 lim ln x = 2 − ζ ( 2 ) = 2 − 6 π 2 ≈ 0 . 3 5 5 Using integration by parts By ∫ a b f ( x ) d x = ∫ a b f ( a + b − x ) d x By ∫ a b f ( x ) d x = ∫ a b f ( a + b − x ) d x Dilogarithm function Li 2 ( z ) = − ∫ 0 z t ln ( 1 − t ) d t also Li s ( z ) = k = 1 ∑ ∞ k s z k ⟹ Li 2 ( 1 ) = k = 1 ∑ ∞ k 2 1 = ζ ( 2 ) , where ζ ( ⋅ ) is Riemann zeta function.
Writing blue-colored texts is difficult and how to write 2 ~s?
We have F ( b ) = ∫ 0 1 ln x ( 1 − x ) b − 1 d x = d a d ∫ 0 1 x a − 1 ( 1 − x ) b − 1 d x ∣ ∣ ∣ a = 1 = ∂ a ∂ B ( a , b ) ∣ ∣ ∣ a = 1 = B ( a , b ) [ ψ ( a ) − ψ ( a + b ) ] ∣ ∣ ∣ a = 1 = Γ ( b + 1 ) Γ ( b ) [ ψ ( 1 ) − ψ ( b + 1 ) ] = b ψ ( 1 ) − ψ ( b + 1 ) and hence ∫ 0 1 ln x ln ( 1 − x ) d x = F ′ ( 1 ) = ( − b 2 ψ ( 1 ) − ψ ( b + 1 ) − b ψ ′ ( b + 1 ) ) ∣ ∣ ∣ b = 1 = − ψ ( 1 ) + ψ ( 2 ) − ψ ′ ( 2 ) = − ( − γ ) + ( 1 − γ ) − ( − 1 + ζ ( 2 ) ) = 2 − ζ ( 2 )
Problem Loading...
Note Loading...
Set Loading...
∫ 0 1 ln ( x ) ln ( 1 − x ) d x = − ∫ 0 1 ln ( x ) n = 1 ∑ ∞ n x n d x = − ∫ ∞ 0 ( − e − t ) ( − t ) n = 1 ∑ ∞ n e − t n d t = ∫ 0 ∞ n = 1 ∑ ∞ n t e − t ( n + 1 ) d t = [ − n = 1 ∑ ∞ n ( n + 1 ) t e − t ( n + 1 ) ] 0 ∞ + ∫ 0 ∞ n = 1 ∑ ∞ n ( n + 1 ) e − t ( n + 1 ) d t = [ − n = 1 ∑ ∞ n ( n + 1 ) e t ( n + 1 ) t ] 0 ∞ + [ − n = 1 ∑ ∞ n ( n + 1 ) 2 e − t ( n + 1 ) ] 0 ∞ = − 0 + 0 − 0 + n = 1 ∑ ∞ n ( n + 1 ) 2 1 = n = 1 ∑ ∞ n ( n + 1 ) 1 − n = 1 ∑ ∞ ( n + 1 ) 2 1 = n = 1 ∑ ∞ ( n 1 − n + 1 1 ) − n = 2 ∑ ∞ n 2 1 = 1 − ( 6 π 2 − 1 ) = 2 − 6 π 2 ≈ 0 . 3 5 5 using series expansion for ln ( 1 − x ) letting x = e − t using integration by parts note that e t ( n + 1 ) > > t , so t → ∞ lim e t ( n + 1 ) t = 0 using telescoping series and the result of the Basel problem